Deteksi Objek Berwarna Merah Secara Real Time Dengan Algoritma Color Filtering - Dewi, Yona Fransiska; Fadillah, Nurul (STMIK Budi Darma, 2019)
The various knowledge and techniques of digital image processing currently available vary greatly. Research and development has been carried out towards object detection and tracking. Color is one of the parameters used to detect and track objects. Humans can distinguish a color, but a computer may not necessarily recognize that color. Digital image processing techniques that can recognize colors, one of which is color filtering. In this study, Color filtering is a technique of processing digital images based on specific colors, detecting and tracking colors by using a web camera (webcam) and red objects. Object Tracking is the process of following an object that moves and moves position, so that the colored object being tracked will draw in realtime with the results of the colors that can be selected.